Maturation of retroviruses - Pornillos, Owen (Curr Opin Virol, 2019)
During retrovirus maturation, processing of the precursor structural Gag polyprotein by the viral protease induces architectural rearrangement of the virus particle from an immature into a mature, infectious form. In this process, the viral RNA genome is encapsidated in a diffusible fullerene capsid that can initiate infection upon entry into the cytoplasm of a host cell. Maturation is an important therapeutic window against HIV-1. In this review, we highlight recent breakthroughs in understanding of the structures of retroviral immature and mature capsid lattices that define the boundary conditions of maturation and provide novel insights on capsid transformation. We also discuss emerging insights on encapsidation of the viral genome in the mature capsid, as well as remaining questions for further study.